Recovery Kitin Dari Limbah Cangkang Rajungan - Muhammad Hazqil Kadzim; Djaenudin Djaenudin; Etih Hartati (Fakultas Teknik, 2020)
The small crab animal is important for the fisheries sector in Indonesia, but usually the small crab industry only takes meat and allows the crab shell to become a pile of waste. To reduce the potential for pollution caused by a small crab shell waste, the waste can be reused to obtain chitin. Small crab shell waste still contains quite a lot of chemical compounds, including protein, minerals (CACO), and chitin. The study conducted chitin extraction with a process preceded by deproteination and then demineralization. Chitin was characterized using Fourier Transform Infra Red (FTIR) and Scanning Electron Microscopy (SEM). The results showed that chitin was successfully extracted from the small crab shell through the deproteination and demineralization process with FTIR l, which results the characteristic spectrum of chitin compounds such as waves of 3433 cm 'for -OH, -NH groups. The absorption around the wave number 3433 cm occurs because of the overlap between the absorption -NH and -OH and the wave number 701 cm 'for the b-1,4-glycosidic group.